HUMAN RIGHTS IN THE PERSPECTIVE OF ADAT LAW - Sepranadja Sepranadja (SAMPURASUN, 2019)
The establishment of Law Number 26 of 2000 concerning the Human Rights Court aims to deal with human rights violations in Indonesia to protect human rights. However, in practice the handling of human rights violations always creates differences of opinion between institutions / human rights enforcement apparatuses, both the National Human Rights Commission, the Public Prosecutor and the competent authorities in addressing human rights violations that occur in Indonesia, which can be seen from the process of several human rights violations from the process investigation. Based on these problems, conducted a descriptive analytical study using a normative juridical approach, namely testing and reviewing secondary data with the library research stage and field studies, then the data were analyzed by qualitative juridical analysis. The results of the study indicate that the concept of handling human rights violations based on the principle of justice through the criminal justice system in Indonesia is carried out by the integrated criminal justice system. That in order to integrate the criminal justice system, one of them is by providing full authority to the National Human Rights Commission in handling cases of human rights violations both at the stage of investigation, investigation and prosecution.